Read between the lines: board gender diversity, family ownership, and risk‐taking in Indian high‐tech firms - Saeed, Abubakr; Mukarram, Syed Shafqat; Belghitar, Yacine (Wiley, 2019)
This article examines the effect of board gender diversity on firm risk‐taking level. Drawing on the contingency framework, we contend that the influence of women executives on firm risk‐taking depends largely on the organizational context of the firm such as the industry in which it operates. To investigate this proposition, we compare the influence of board gender diversity on firm risk‐taking level in Indian high‐tech and in non‐high‐tech sectors. Our findings indicate that female executives operating in high‐tech sectors take more risk than their counterparts female executives who operate in non‐high sector. Interestingly, our analysis also reveals that family ownership negatively moderates the impact of female executives on risk‐taking in high‐tech firms. In additional analysis, we find that female executives exert a positive impact on firm performance only in high‐tech sector. This suggests that the influence of female executives on firm outcomes is not always straightforward.
Keywords: board gender diversity; high-tech sector; risk-taking; uncertainty